1998
DOI: 10.1002/(sici)1521-3757(19981102)110:21<3176::aid-ange3176>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Supramolekulare Aggregate heterogener Multiporphyrinanordnungen – die Strukturen von [{ZnII(tpp)}2(tpyp)] und dem Koordinationspolymer [{[MnIII(tpp)]2(tpyp)(ClO4)2}∞]

Abstract: 46% des Kristallvolumens machen Kanäle aus: Aus [MnIII(tpp)]⋅ClO4 und tpyp bildet sich ein zweidimensionales Koordinationspolymer von außergewöhnlicher Regelmäßigkeit (siehe schematische Darstellung; tpp=Tetraphenylporphyrin, tpyp=Tetrapyridylporphyrin). Durch die Kristallpackung dieser Polymere entsteht eine offene Endlosstruktur mit Netzen rechtwinkliger Kanäle, die mit Nitrobenzol als Solvens gefüllt sind. Bei der Reaktion von [ZnII(tpp)] mit tpyp entstehen hingegen nur oligomere Strukturen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The pioneering work of Robson and co‐workers in this area has, indeed, shown that metalloporphyrins can give coordination networks with the CdSO 4 5a or the PtS topology5b by using Cd II centers (acting as linear spacers) or tetrahedral Cu I centers, respectively. Most of the reported frameworks contain external divalent metal ions, while species with trivalent6e, 8 or monovalent6ad metal ions are more rare.…”
Section: Methodsmentioning
confidence: 99%
“…The pioneering work of Robson and co‐workers in this area has, indeed, shown that metalloporphyrins can give coordination networks with the CdSO 4 5a or the PtS topology5b by using Cd II centers (acting as linear spacers) or tetrahedral Cu I centers, respectively. Most of the reported frameworks contain external divalent metal ions, while species with trivalent6e, 8 or monovalent6ad metal ions are more rare.…”
Section: Methodsmentioning
confidence: 99%
“…6). The binding energy of coordination bonds is typically within 120-250 kJ mol 21 , making them most effective in the synthesis of stable network arrays. Moreover, the carboxylic groups can be readily deprotonated in neutral and basic environments to yield anionic porphyrin units, and balance the charge introduced by the cationic metal bridges.…”
Section: Network Sustained By Metal-ligand Coordinationmentioning
confidence: 99%
“…8a). 21 Its major significance lies in the fact that further metallation of the free-base porphyrins can result in continuous multiporphyrin patterns with different metal ions and oxidation states, which in turn can be useful in chargetransfer processes. Yet, such systems could not be crystallized as yet.…”
Section: Network Sustained By Metal-ligand Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering work of Robson and co‐workers in this area has, indeed, shown that metalloporphyrins can give coordination networks with the CdSO 4 5a or the PtS topology5b by using Cd II centers (acting as linear spacers) or tetrahedral Cu I centers, respectively. Most of the reported frameworks contain external divalent metal ions, while species with trivalent6e, 8 or monovalent6ad metal ions are more rare.…”
Section: Methodsmentioning
confidence: 99%